Implementing Electronic Document and Record Management Systems - Adam, Azad (CRC Press, 2009)
The global shift toward delivering services online requires organizations to evolve from using traditional paper files and storage to more modern electronic methods. There has however been very little information on just how to navigate this change-until now. Implementing Electronic Document and Record Management Systems explains how to efficiently store and access electronic documents and records in a manner that allows quick and efficient access to information so an organization may meet the needs of its clients.